1986
DOI: 10.1007/bf00291612
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of coagulation factor XIII B subunit in the Japanese population: description of three new rare alleles

Abstract: Polyacrylamide gel isoelectric focusing (PAGIEF) of neuraminidase-treated EDTA plasma samples followed by electroblotting with enzyme immunoassay was performed to further investigate coagulation factor XIII B subunit (FXIII B) polymorphism. In 435 Japanese subjects PAGIEF patterns of FXIII B were classified into five common and three rare allotypes. This suggested that the FXIII B*2 allele existed in the Japanese population in the same manner as in Caucasians. Three new rare allotypes were considered to be con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Plasma desialylated overnight at 25°C with neuraminidase (1 U/ml in 0.005 M sodium acetate buffer, pH 5.5) was used for typing F13B, ORMl, and AHSG after Nakamura et al (1986) and Yuasa et al (1987). In each case, several modifications were made as previously described (Scacchi et al 1991(Scacchi et al , 1992.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma desialylated overnight at 25°C with neuraminidase (1 U/ml in 0.005 M sodium acetate buffer, pH 5.5) was used for typing F13B, ORMl, and AHSG after Nakamura et al (1986) and Yuasa et al (1987). In each case, several modifications were made as previously described (Scacchi et al 1991(Scacchi et al , 1992.…”
Section: Methodsmentioning
confidence: 99%
“…The IF locus is assigned to chromosome 4q25 and linked to alcohol dehydrogenase sub units [Shiang et al, 1989], Since Nakamu ra and Abe [1985] first demonstrated the 2 common IF alleles (IF*A and IF*B) using isoelectric focusing (IEF), the 2 rare alleles 1F*C and IF*AI have been identified in Canadian [Zhou and Larsen, 1989] and in Japanese [Nakamura and Sawaguchi, 1990], respectively. This paper describes the IF allele fre quencies in a Chinese, a Korean and a Japanese population.…”
Section: Introductionmentioning
confidence: 99%
“…The population studied is in genetic equilibrium assuming the HardyWeinberg hypothesis. When compared with those obtained in various other populations [1][2][3][4][5][6][9][10][11][12], our results in Libyans showed marked differences in the frequencies of the three common alleles FXIIIB*I, FXIIIB*2, FXIIIB*3 and the occurrence of a fourth common allele, FXIIIB*6. Further investigations in other Arab populations will clarify whether the FXIIIB*6 allele is specific for Libyans or a characteristic marker for Arabs.…”
Section: Immunoblottingmentioning
confidence: 71%
“…Several rare alleles have been reported since Board's original publication: FXIIIB*4 [2], FXIIIB*5 [3], FXIIIB*6, FXIIIB*7, FXIIIB*8, FXIIIB*9 and FXIIIB*10 [4], FXIIIB*13, FXIIIB*14 and FXIIIB*15 [5], FXIIIB*16, FXIIIB*17, FXIIIB*18, FXIIIB*19, FXIIIB*20, FXIIIB*21 and FXIIIB*22 [6]. To the authors knowledge, the alleles FXIIIB*5, FXIIIB*7, FXIIIB*8, FXIIIB*9 and FXIIIB*10 have been reported, but the ethnic origin and gene frequencies were not given.…”
Section: Introductionmentioning
confidence: 99%